Statins: the potential in treating alzheimer’s disease (Experimental biology, 2015)
Alzheimer’s disease (AD) is a widespread chronic neurodegenerative disease which affects people of 65 and older. Currently, there are no known effective methods of treatment of AD. However, the epidemiological data suggests that prolonged use of cholesterol lowering drugs such as statins decreases the risk of AD development. In this literature review we propose several basic mechanisms which can be involved in prevention of AD development by statins. These mechanisms include control of cholesterol synthesis, regulation of enzymes, which participate in β-amyloid synthesis, and suppression of inflammation in brain blood vessels. Nevertheless, the therapeutic effect of statins on AD and their use for AD prevention is still an open question and needs further investigation.
Keywords: amyloid; statins; cholesterol; hematoencephalic barrier